Optimum Frequency—Its Relevance and Measurements - NP, Nataraja (Journal of All India Institute of Speech and Hearing)
This paper discusses the importance of ’optimum pitch ’ in the diagnosis and therapy with the voice disorders. The merits and the demerits of methods of measuring optimum pitch and the development of an objective method of locating optimum pitch have also been discussed. Experimental findings supporting that there is maximum physioacoustic economy at the optimum pitch as located by an objective method of locating optimum pitch have been presented. An attempt has also been made to indicate the possible classification of voice disorders based on the optimum pitch